Exploring the feasibility of solvent recirculation in the extraction process of (poly)phenols from elderflower (Sambucus nigra L.) - Vasiljević Nebojša; Mićić Vladan; Petrović Zoran; Kostić Duško; Palangetić Nikolina; Vuković Jelena (Reciklaža i Održivi Razvoj)
The traditional maceration technique with a two-step solid-liquid extraction was used in this paper. After the first extraction step, an extract was separated from the exhausted plant material (elderberry flower) and then a plant material was added to the extract. Experimental parameters included different ethanol concentrations (30 %, 60 %, and 90 %), solid-to-solvent ratios (1:15, 1:30, and 1:45 w/v), pH values (3, 7, and 10), and extraction times (15, 30, and 45 minutes), while one-factor-at-a-time (OFAT) was experimental design. The results indicated that the optimal ethanol concentration in the solvent was 60 vol. % for both extraction steps. Increasing the solid-to-solvent ratio from 1:15 w/v to 1:30 w/v resulted in higher (poly)phenol content, with a slight decrease observed at higher ratios. (Poly)phenols content remained consistent in acidic and neutral environments, but decreased at pH 10. While the content of (poly)phenolic compounds increased with longer extraction times, 30 minutes was considered optimal, as further extension did not significantly increase the content. Additionally, it was observed that the content of total (poly)phenols was lower in the second extraction step, suggesting saturation of the solvent after the first extraction..